The Quality of Life of Wives Married with Belis: Reviewed from Resilience and Self-Esteem - Paula Kristiani Widyaningsih Kale Lado (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to determine the relationship between resilience and self-esteem with the quality of life of wives married with belis. The subjects of this study were 267 wives who married with belis in Maulafa Subdistrict, Kupang City, East Nusa Tenggara. Cluster random sampling was used as a sampling technique and the data analysis used was Spearman-Brown analysis. The results showed that there was a significant positive relationship between resilience and quality of life. The higher the resilience, the higher the quality of life of the wife who married with belis. There is a significant positive relationship between self-esteem and quality of life. the higher the self-esteem, the higher the quality of life of the wife who married with belis